PENGARUH PERTUMBUHAN SELF ASSESSMENT SYSTEM, PEMERIKSAAN PAJAK DAN PENAGIHAN PAJAK TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI (PPN) PADA KPP PRATAMA BALIKPAPAN - Satriawaty Migang; Wani Wahyuni (Fakultas Ekonomi Universitas Pekalongan, 2020)
This study aims to examine the effect of the Growth of Self Assessment System, Tax audit and Tax billing to Value Added Tax Revenue (VAT) on a partial and simultaneously. The research uses quantitative methods. Research data are 36 companies in 2014-2016. The analysis is multiple linear regression and the classical assumption test with the help of SPSS version 23 application. Partial research results show that the Growth of Self Assessment System has an effect on Value Added Tax Revenue. While the tax audit and tax billinghave no significant effect on the Value Added Tax (VAT). But simultaneously or together Growth Self Assessment System, Tax audit and Tax Billing have an influence on Value Added Tax (VAT) Revenue.Keywords: Growth of Self Assessment System, Tax Audit, Tax billing, and Value Added Tax (VAT).